Profil Materi Ajar IPA Berbasis Humanistis untuk Kelas VII SMP Topik Besaran dan Satuan (Hasil Pengembangan) - Sudarto, Sudarto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to obtain the profile of Science teaching materials for junior high school on the topic of Quantities and Units based on humanism. Science teaching materials for junior high school on the topic of Quantities and Units based on humanism that have been produced have many advantages compared to the other teaching materials. The main advantage is that this teaching material brings the students to a condition of comprehensive self-development of students, namely the development of intellectual, creative, emotional, and spiritual potential. This teaching material was developed through research and development of the 4D Model (definition, design, development, and dissemination) which was carried out by involving 7th Grade students of SMPN 24 Makassar in the 2008/2009 academic year for the limited trial stage, extensive trial and effectiveness test. The products produced in this study have gone through the planning process, material testing by material experts, revision, product testing, and effectiveness testing on the students. Research results: the profile of the presentation of the Science Teaching Material on the Topic of Quantities and Units Based on Humanism that has been obtained through development includes: the initial part (consisting of words of encouragement to learn, advice so that students are increasingly aware of the importance of learning and studying the topic of Quantities and Units), the middle part (consisting of the topic title, indicators to be achieved in studying the topic of Quantities and Units, the content of the Quantities and Units Material, the presentation of attitudes that will be developed in students in learning with the topic of Quantities and Units, and suggestions or tasks that students must do related to the Quantities and Units material that has been read and studied), and the final part (consisting of Learning questions for Practice in order to develop intellectual, creative, emotional and spiritual potential).